Pharmaceutical care in the use of contraceptive methods: a narrative review (Research, Society and Development, 2021)
Objective: Discuss pharmaceutical care regarding the use of contraceptive methods. Method: A narrative literature review was carried out, consulting publications between 2000 and 2021 on virtual platforms. Results: All products and methods are associated with potential benefits and complications that must be considered with the patient and healthcare professionals in selecting the most satisfactory option. Pharmaceutical care in guidelines for contraceptive methods should begin by investigating the patient's health history, identifying conditions or characteristics related to the safety of the hormonal contraceptive. Thus, pharmacists provide drug counseling and health education as the patient begins their contraceptive evaluation and continued adherence and tolerability during subsequent deliveries. Conclusion: There is a wide variety of medications used in contraception, and this can cause patients to have many doubts about the best choices for use. Therefore, the relationship between pharmacist and patient becomes essential for successful pharmacotherapy. It is essential that pharmacists provide clear information about the best way to carry out the treatment with contraceptive methods, in addition to clarifying the correct ways to use drugs, also showing possible contraindications and drug interactions, effectively contributing to minimize the risks medication and adverse reactions. Therefore, pharmaceutical care will promote personalized, humanized and scientifically correct care regarding the use of contraceptive methods.